An energy efficient and secure data forwarding scheme for wireless body sensor network. (22nd August 2019) - Kumar, A. Dinesh; Smys, S.
Monitoring human bodies and collecting physiological information are the major healthcare applications for wireless body area networks (WBANs). Due to the limited energy resource of body sensors, their energy depletions will cause severe network performance degradation such as latency and energy efficiency. To solve this problem existing system introduced an energy-efficient data forwarding strategy (EDFS) to balance sensor energy consumption, improve network lifetime and collaborative operations of heterogeneous WBANs. However, the existing system only considered the energy function for optimal relay sensor node selection, does not considered the delay and hop count of node. Hence in this system, the TOPSIS-based artificial bee colony algorithm (TOPSIS-based ABC) is proposed to select the optimal path for data transmission. In order to reduce the network congestion compressed sensing (CS) is performed. To provide high security for patient related data hybrid RSA and Diffie-Hellman algorithm is used. The proposed methodology is implemented by using NS-2 simulator.